Use of dietary and performance-enhancing supplements among male fitness center members in Riyadh: A cross-sectional study. - Yazed AlRuthia; Bander Balkhi; Marwan Alrasheed; Ahmed Altuwaijri; Mohammad Alarifi; Huda Alzahrani; Wael Mansy (PLoS ONE)
This study aimed to explore the health beliefs and patterns of dietary supplement usage among fitness center members. This cross-sectional study was conducted in four large indoor fitness centers in Riyadh, Saudi Arabia. This study involved male fitness center members aged ≥18 years with no speech or hearing disabilities. In-person interviews were conducted with fitness center members who agreed to participate using a newly developed questionnaire. Information on participants' sociodemographics (e.g., age and education), smoking status, health status, exercise frequency, average time spent exercising, different supplements used, used supplements sources, and health beliefs regarding dietary supplements were obtained. A total of 445 fitness center members agreed to participate, and 198 of them reported taking dietary supplements. Most participants were between the age of 18 and 25 years (66%), had a college degree (74%), non-smokers (77%), healthy (84%), and perform exercise at least thrice weekly (52%) for at least 1 hour (63%). The percentage of participants who had favorable health views on dietary supplements was significantly higher among the supplement users than among the non-users (P<0.0001). Proteins, multivitamins, amino acids, and omega 3 fatty acids were the most commonly reported supplements used. Almost 30% of the supplement users reported buying them overseas, 28% online, 25% from a pharmacy or supplement store, 19% from a medical clinic, and 17% from peddlers. Public health campaigns are needed to educate the public on the potential harmful effects of supplements if purchased from an unofficial seller or taken without seeking medical advice before using them.